The online global quarantine conversation club as the way to trigger students’ ability in speaking English - Suswanto, Totok Indra (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Global Quarantine Conversation Club (GQCC) is a speaking practice program that involves more than 20 countries across the world. Since the English subject has not attracted students’ attention yet, this program is expected to trigger the students in learning English. The study purposed to describe the implementation of GQCC, to analyze the students’ perception toward the implementation of GQCC, and to analyze the teacher’s reflection toward the implementation of GQCC. This study belonged to qualitative research approach with case study design. One English teacher and two students of a senior high school in Gresik, Indonesia, were selected as the subjects of the study. The instruments used in this study were observations, interviews, and documentations. The result showed that (1) the teachers and the students’ activities were doing briefing and rehearsal in pre-program, doing presentation and group discussion during program and doing evaluation and reflection in post program, (2) the students found that the GQCC program gave positive impact on their English as well as gave them new cultural knowledge, and (3) the teacher was becoming aware about the need of improving the students’ speaking skill through some accelerated programs as well as the technology literacy. This study gave some recommendations for both school and further research.